Band alignments of sputtered dielectrics on GaN. (12th December 2019) - Supardan, S N; Das, P; Major, J D; Hannah, A; Zaidi, Z H; Mahapatra, R; Lee, K B; Valizadeh, R; Houston, P A; Hall, S; Dhanak, V R; Mitrovic, I Z
Abstract: The band alignments of sputtered ZrO2, Al2 O3 and MgO on GaN have been measured experimentally using x-ray photoelectron spectroscopy (XPS). The valence band offsets (±0.2 eV) for ZrO2, Al2 O3 and MgO on GaN using Kraut's method and charge-corrected XPS core levels were found to be 0.4 eV, 1.1 eV and 1.2 eV with corresponding conduction band offsets (±0.2 eV) of 1.3 eV, 2.0 eV and 2.8 eV, respectively. The electrical characterization of metal insulator semiconductor (MIS)-capacitors with different gate dielectrics (ZrO2, Al2 O3 and MgO) has been performed as well. The current density of the MIS-capacitors with gate dielectrics MgO and Al2 O3 at a positive bias of 1 V show lower leakage currents of 3.2 × 10 −6 A cm −2 and 5.3 × 10 −6 A cm −2 respectively, whereas, the MIS-capacitors with ZrO2 gate dielectric have the highest leakage current of 6.2 × 10 −4 A cm −2 at 1 V.